Cavitation induced starvation for piston-ring/liner tribological conjunction. - Chong, William Woei Fong; Teodorescu, M.; Vaughan, Nicholas D. (Elsevier, 2011)
The study investigates the mechanism of ring-liner lubrication in the vicinity of the top and bottom dead centres of an internal combustion engine. Predicting lubricant transient behaviour is critical when the inlet reversal leads to thin films and inherent metal-to-metal interaction. It was found that the cavitation, which is located at the trailing edge of the contact before reversal, briefly survives after reversal as a confined bubble at the leading edge. This depletes the film promoting starvation. Several algorithms were compared. It is concluded that the lubricant film is thinner than initially thought.
Keywords: Pistonring; lubrication; tribology; Elrod cavitation algorithm; cavitation; starvation